Case Report: Hemoptysis Caused by Pulmonary Tuberculosis Complicated With Bronchial Artery-Pulmonary Artery Fistula in Children - Zhu, Huihui; Lv, Fangfang; Xu, Ming; Wen, Shunhang; Zheng, Yangming; Zhang, Hailin (Frontiers in Pediatrics, 2021)
Two children with pulmonary tuberculosis complicated with bronchial artery-pulmonary artery fistula presented to our hospital from 2016 to 2020. Bronchial artery-pulmonary artery fistula is a rare pulmonary vascular malformation, which can be congenital or acquired. The common causes of acquisition include chronic pulmonary inflammation and neoplasm.